Improving large taxpayers' compliance : a review of country experience - Baer, Katherine...[et al.] (IMF WashingtonUS, 2002)
Provides an overview of the role, structure and functions of large taxpayer operations in about 40 countries. Reviews the effectiveness of large taxpayer units in selected developing and transition countries.